The Time Fetch - Herrick, Amy. (Chapel Hill, NC : Algonquin Young Readers, 2013)
When the Time Fetch's foragers gobble up too much time, causing the fabric of the universe to unravel and blur the boundaries between worlds and dimensions, eighth-grade loner Edward and his classmates must band together to save the day.
Keywords: Space and time -- Juvenile fiction; Action and adventure fiction; Science fiction